Impact of Indarbela quadrinotata on the Growth of Casuarina equisetifol1a - Sasidharan, K. R.; Varma, R. V.; Sivaram, M. (Indian Forester, 2010)
Several insect pests are associated with Casuarina equisetifolia L. in India. Among them, the bark eating caterpillar, Indarbela quadrinotata Walker (Metarbelidae: Lepidoptera) has attained serious pest proportions in Tamil Nadu State, which is located in the southern part of the country. The impact of I. quadrinotata on the growth of C. equisetifolia was studied in selected plantations of this species, located in three agro-climatic zones of the State. The data generated suggest that I. quadrinotata has the potential to reduce the growth of the trees significantly.